Potret Pendidikan Islam di Pamekasan Madura (Peran KH. Ahmad Madani dalam Pendidikan dan Pengembangan Masyarakat di Ponpes Sumber Bungur Pamekasan Madura 1960-2006) - Mohammad Sholeh (UIN Sumatera Utara Medan, 2018)
This study describes the role of KH. Ahmad Madani in education and community development at boarding school of Sumber Bungur. The method used in this study is the historical method, which uses a biographical approach. Biographical approach is an approach that seeks to understand and deepen keperibadian (figures) based on the background of the cultural social environment in which the character was raised, how the education process is experienced, the characters that are around him. The technique of data collection is by literature study and interview. The author collects data related to the discussion that will the author do. Data collected from interviews, books, journals, theses, internet and articles. The writer then criticized the source that has been obtained, which then performed data analysis and taken conclusions. The results of this study is Ahmad Madani is a pioneer and a figure who care about the education system in Madura, especially in Pakong Pamekasan District. From his ideas, around the 1960s, he was able to integrate both educational systems by establishing his own schools where religious knowledge and common knowledge were taught, although at the beginning of his pioneering many societies and even religious leaders considered KH. Ahmad Madani has continued the heritage and culture of Dutch clones, by incorporating the general materials into the educational institution he pioneered. Whereas the general matter is a subject matter brought by westerners whose connotation is that the western man is a Gentile.Keywords : Pesantren Education, Education in Ponpes Sumber Bungur.